Biomechanical properties of canine staphylectomies closed with barbed or smooth suture. Issue 1 (24th November 2020) - Gleason, Hadley E.; Phillips, Heidi; McCoy, Annette M.; Gutierrez‐Nibeyro, Santiago D.; McKiernan, Brendan C.; Duffy, Daniel J.; Feign, Ian M.; Kim, Woojae Jason; Kersh, Mariana E.
Abstract: Objective: To compare the duration of closure and biomechanical properties of staphylectomies closed with absorbable bidirectional barbed suture or smooth monofilament suture in a simple continuous or interrupted pattern Study design: Ex vivo study Sample population: Soft palates (n = 60) harvested from mesaticephalic canine cadavers Methods: One centimeter of tissue was excised from the caudal border of each soft palate, and the oral and nasopharyngeal mucosal surfaces were apposed with 2‐0 bidirectional Quill Monoderm knotless closure device barbed suture (Q), 3‐0 Monocryl in a simple continuous (MC) pattern, or 3‐0 Monocryl in a simple interrupted (MI) pattern (n = 20 per group). Duration of closure was compared between groups. Tissues were tested under tension to failure, and mode of failure data were collected by video capture. Results: Closure time was longer for MI closures than for Q and MC closures, with means of 259.9, 215.4, and 196.7 seconds, respectively ( P < .0001). No difference was detected in yield force, force to first tissue rupture, maximum force, and energy required for yield and maximum force between groups. Energy to yield was 190.0, 167.8, and 188.95 N‐mm for MI, Q, and MC closures, respectively. Conclusion: Biomechanical properties of staphylectomies closed with barbed or smooth sutures did not differ in this cadaveric model. Clinical significance: Barbed suture can be considered as an alternative for closure of canine staphylectomies. These results provide evidence to justify additional research to evaluate clinical outcomes in dogs undergoing staphylectomy.